The complex evolutionary history of apricots: Species divergence, gene flow and multiple domestication events. Issue 24 (22nd November 2019) - Liu, Shuo; Cornille, Amandine; Decroocq, Stéphane; Tricon, David; Chague, Aurélie; Eyquard, Jean‐Philippe; Liu, Wei‐Sheng; Giraud, Tatiana; Decroocq, Véronique
Abstract: Domestication is an excellent model to study diversification and this evolutionary process can be different in perennial plants, such as fruit trees, compared to annual crops. Here, we inferred the history of wild apricot species divergence and of apricot domestication history across Eurasia, with a special focus on Central and Eastern Asia, based on microsatellite markers and approximate Bayesian computation. We significantly extended our previous sampling of apricots in Europe and Central Asia towards Eastern Asia, resulting in a total sample of 271 cultivated samples and 306 wild apricots across Eurasia, mainly Prunus armeniaca and Prunus sibirica, with some Prunus mume and Prunus mandshurica . We recovered wild Chinese species as genetically differentiated clusters, with P. sibirica being divided into two clusters, one possibly resulting from hybridization with P. armeniaca . Central Asia also appeared as a diversification centre of wild apricots. We further revealed at least three domestication events, without bottlenecks, that gave rise to European, Southern Central Asian and Chinese cultivated apricots, with ancient gene flow among them. The domestication event in China possibly resulted from ancient hybridization between wild populations from Central and Eastern Asia. We also detected extensive footprints of recent admixture in all groups of cultivated apricots. Our results thus show that apricot is an excellent model for studying speciation and domestication in long‐lived perennial fruit trees.